A Case of Amiodarone-Induced Thyrotoxicosis: A diagnostic and therapeutic dilemma - Sudheer Ahamed, PS (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2009)
Amiodarone is an iodine rich agent widely used for the treatment of ventricular arrhythmias, paroxysmal supraventricular tachycardia, atrial fibrillation and flutter. However 14–18% of patients treated with amiodarone develop overt thyroid dysfunction in the form of either amiodarone-induced thyrotoxicosis (AIT) or amiodaroneinduced hypothyroidism (AIH). Two different types of AIT have been recognised and designated as Type 1 and Type 2. Distinguishing between the two is often difficult, but necessary for instituting appropriate treatment. We report a case of a 56 year-old male patient who was started on amiodarone for atrial fibrillation and then developed AIT. The challenges in the diagnosis and management of these patients are discussed.